Meteo Read: Client Software for Inserting Observed Atmospheric Data into MySQL\(_{TM}\) Database - Szabó-Takács , Beáta; Takács , Tamás; Rocek , Ales (Theory and Applications of Engineering Research Vol. 2, 2024)
This chapter investigates the tendency of climate change and its effects on ecology, economy and sociology is essential for long-term policy making. High-quality data for these investigations is provided by the long-term, state-of-the-art instrumentation measurements of the atmospheric properties, both chemical and physical. MeteoRead is a client database software that imports the observed atmospheric data, e.g. wind direction, wind speed, aerosol particle concentration, etc. and makes them available in different file formats most commonly used in climate research. MeteoRead was developed in JavaTM language. One of the most significant benefits of JavaTM language is its platform independence, as the development and execution are available on almost all devices. JavaTM is an object-oriented language where the created objects remain available throughout the runtime thanks to its memory-handling technique. This JavaTM-based program applies the Structured Query Language (SQL) functions such as table creation on a database server, data or figures insertion into the table and data selection via Graphical User Interface. The selected data can be stored in NetCDF, HDF5, DataBase or TXT file formats, and the figures can be available in PNG, JPG, JPNG, PDF or GIF file formats. The program was tested on Linux and Windows platforms with different JavaTM Development Kit. The structure of the software was demonstrated thoroughly in this chapter. Finally, it was concluded that MeteoRead, a client database software, importing observed atmospheric data and figures, and for also filtering and exporting the data in the most commonly applied file formats such as NetCDF, HDF5, DataBase, and TXT and the figures in PNG, JPG, JPNG, PDF and GIF formats. Monthly, yearly as well as hourly average data value can be used to visualized through the MeteoRead. It can be used in the functionality of the SQL database to calculate various mathematical and statistical correlations.